2012
DOI: 10.1007/s00240-012-0501-3
|View full text |Cite
|
Sign up to set email alerts
|

Unique surface and internal structure of struvite crystals formed by Proteus mirabilis

Abstract: Crystallization of struvite from artificial urine in the presence of Proteus mirabilis microorganisms depends strongly on pH value. At small value of pH, struvite yields crystals of coffin-like habit with very specific structure. The analysis using scanning electron microscopy shows that the crystals possess well-defined faces, but higher magnifications show very specific structuration as if the crystals were built from small three-dimensional subunits. The possible role of microorganisms in the formation of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 24 publications
7
76
0
2
Order By: Relevance
“…It is suggested that bacteria play important role in directing the struvite surface structuration. The results [7] also show porous internal structure of struvite characteristic only for the growth in the presence of bacteria. Similar results have also been reported for other crystals.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…It is suggested that bacteria play important role in directing the struvite surface structuration. The results [7] also show porous internal structure of struvite characteristic only for the growth in the presence of bacteria. Similar results have also been reported for other crystals.…”
Section: Introductionmentioning
confidence: 83%
“…The solution of artificial urine used during crystal growth experiments was made from the following components [11] [7,12]. The artificial urine was prepared by dissolving chemicals (Sigma Aldrich) of reagent-grade purity in redistilled water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Struvite shows very characteristic structuration suggesting its porous nature. This issue is known and has been described in the literature [33,34]. Figure 1d,e shows the obtained precipitate in the absence of bacteria and in the case when the composition of artificial urine is modified (without magnesium chloride hexahydrate) so that no formation of struvite takes place; only the precipitate which is the subject of our interest occurs.…”
Section: General Characterization Of Precipitatesmentioning
confidence: 93%
“…92 olduğuna dair güçlü kanıtlar vardır. 87 Hayvansal proteinlerdeki sülfür içeren aminoasitler sülfürik asit şeklinde vücutta asit yüküne neden olmaktadır.…”
Section: Hayvansal Proteinlerunclassified